2011
DOI: 10.18388/abp.2011_2256
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of FAD-dependent monooxygenase activity from aromatic compounds-degrading Stenotrophomonas maltophilia strain KB2.

Abstract: The purpose of this study was purification and characterization of phenol monooxygenase from Stenotrophomonas maltophilia strain KB2, enzyme that catabolises phenol and its derivatives through the initial hydroxylation to catechols. The enzyme requires NADH and FAD as a cofactors for activity, catalyses hydroxylation of a wide range of monocyclic phenols, aromatic acids and dihydroxylated derivatives of benzene except for catechol. High activity of this monooxygenase was observed in cell extract of strain KB2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The isolation, purification, and analysis of genetic and biochemical properties revealed that the S. maltophilia KB2 strain contains enzymes belonging to oxygenases: phenol monooxygenase [ 28 ] and catechol 2,3-dioxygenase [ 29 ]. Phenol monooxygenase is the enzyme that takes part in the key step of phenolic compound decomposition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The isolation, purification, and analysis of genetic and biochemical properties revealed that the S. maltophilia KB2 strain contains enzymes belonging to oxygenases: phenol monooxygenase [ 28 ] and catechol 2,3-dioxygenase [ 29 ]. Phenol monooxygenase is the enzyme that takes part in the key step of phenolic compound decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum activity of the enzyme occurs at pH 7.2 and a temperature of 30 °C. The activity of the monooxygenase of the KB2 strain is associated with the cytochrome system [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The activity of monooxygenase and catechol 1,2-dioxygenase was observed in the crude extracts from each monosubstrate culture (Table 1). The higher activity of monooxygenase in the presence of ibuprofen, phenol and benzoate reveals hydroxylation, the first step of aromatic compound degradation (Wojcieszyńska et al 2011b), while the activity of catechol 1,2-dioxygenase indicates ortho cleavage of the aromatic ring of these compounds (Guzik et al 2013). In the presence of 4-hydroxybenzoate as an inductor, the activity of monooxygenase and catechol 1,2-dioxygenase was significantly lower than in the control culture with glucose (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Two of the most important enzymes involved in salicylate decomposition are salicylate 1-hydroxylase and salicylate 5-hydroxylase (monooxygenases). Salicylate monooxygenases belong to one of the three groups of hydroxylating oxygenases—activated-ring monooxygenases (Wojcieszyńska et al 2011 ). The general structure of these groups includes a three-component protein with separate functional units: reductase with a flavin cofactor, ferrodoxin with a Rieskie-type iron-sulfur cluster [2Fe-2S] and hexamer-built α 3 β 3 terminal oxygenase with [2Fe-2S] a cluster and one nonheme iron(II) per α subunit (Mason and Cammack 1992 ; Bertini et al 1996 ).…”
Section: Acetylsalicylic Acid Biodegradation By Microorganismsmentioning
confidence: 99%